DESAIN APLIKASI ALQURAN BERBASIS ANDROID â€œSAHABAT NUSAâ€ - Nurul Izza, Ayu Adista; Azzahra, Alifia; Maharani, Shella (Universitas Islam Sultan Agung, 2020)
The development of technology at this time has developed rapidly. Several Android-based applications have been created and used in various fields. One of them is in the field of learning through gadgets. Android applications for learning quite a lot make it easier to carry out various activities to support productivity. It cannot be denied that gaming is one of the big industries today. Games can be an alternative entertainment to fill spare time and be a very fun activity for children. Various kinds of games currently being developed are based on Desktop / PC (Windows, Linux, Mac, etc.), Mobile (Symbian, Java, Android, iOS), and Web-based (HTML5, Flash). One type that is developing currently is RPG (Role Playing Game) because besides being popular and much in demand by game players, RPG is a type of game that is simple and fun to play. This RPG game contains various features and has an interesting game play. When one examines the necessity to learn the Alquran with technological developments, as well as its popular features, an idea is born to create a new learning innovation that can make it easier for children to learn and understand the Qur'an. This game was created using the RPG Maker VX Ace Game engine with the Ruby programming language because of its simplicity and high level of flexibility. This RPG Maker VX Ace game engine adopts an event script system, where events are specified in the map.Â Keywords: Alquran, Aplication, Android